The Female Principals’ Transformational Leadership in Implementing School-Based Management in Public and Private Senior High Schools of Berau Regency - Herjayanti, Risna; Komariyah, Laili; Akhmad, Akhmad (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
The role of leadership, especially the transformational leadership of the principal, plays a crucial role in driving the implementation of school-based management. This study aims to describe and analyze the transformational leadership characteristics of female principals in the implementation of School-Based Management in public and private high schools in Berau Regency. The research method used is qualitative with a case study approach, as the research subjects are female principals at SMAN 12 Berau and SMAIT Ash Shohwah. Data were collected using interview, observation, and documentation techniques. The data was then analyzed with a cycle of data collection, data presentation, data reduction and conclusion drawing. As for the implementation of School-Based Management, the researchers focused on the components of educators and education personnel, school and community relations. The results showed the leadership characteristics of female principals in SMAN 12 Berau and SMAIT Ash Shohwah as follows: (1) Leading with exemplary and high empathy, (2) Providing inspiring motivation, (3) Building collaboration and monitoring the activities of educators and education personnel so as to create a conducive climate, (4) Building a solid team with a positive interpersonal approach. The conclusion of this study is that the transformational leadership of female principals contributes positively to the effectiveness of MBS implementation, especially in improving the quality of education and school performance. The implication of this finding can be the basis in the development of education policy.